2021
DOI: 10.3389/fpsyt.2021.718485
|View full text |Cite
|
Sign up to set email alerts
|

The Phenotypic Profile Associated With the FMR1 Premutation in Women: An Investigation of Clinical-Behavioral, Social-Cognitive, and Executive Abilities

Abstract: The FMR1 gene in its premutation (PM) state has been linked to a range of clinical and subclinical phenotypes among FMR1 PM carriers, including some subclinical traits associated with autism spectrum disorder (ASD). This study attempted to further characterize the phenotypic profile associated with the FMR1 PM by studying a battery of assessments examining clinical-behavioral traits, social-cognitive, and executive abilities in women carrying the FMR1 PM, and associations with FMR1-related variability. Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 128 publications
(209 reference statements)
3
14
0
Order By: Relevance
“…Cluster 1 represented a psychiatric feature group (27% of our sample); Cluster 2 represented a group with executive dysfunction and elevated high frequency (gamma) neural oscillatory activity (32%); and Cluster 3 represented a relatively unaffected group (41%). These represent three clinicallymeaningful clusters with good clinical face-validity (Hagerman et al, 2018) and considerable overlap with clusters recently identified by Maltman et al (2021). Psychiatric features and executive dysfunction have been welldocumented in female PMCs; however, the majority of previous studies have examined these features independently (for review see Hagerman et al, 2018).…”
Section: Cluster Membershipmentioning
confidence: 93%
See 3 more Smart Citations
“…Cluster 1 represented a psychiatric feature group (27% of our sample); Cluster 2 represented a group with executive dysfunction and elevated high frequency (gamma) neural oscillatory activity (32%); and Cluster 3 represented a relatively unaffected group (41%). These represent three clinicallymeaningful clusters with good clinical face-validity (Hagerman et al, 2018) and considerable overlap with clusters recently identified by Maltman et al (2021). Psychiatric features and executive dysfunction have been welldocumented in female PMCs; however, the majority of previous studies have examined these features independently (for review see Hagerman et al, 2018).…”
Section: Cluster Membershipmentioning
confidence: 93%
“…Previous studies have documented both intact and impaired executive function, social processing, and psychiatric features of depression and anxiety in female PMCs without FXTAS relative to age-and sex-matched typicallydeveloping controls (TDCs) (Bennetto et al, 2001;Hessl et al, 2001;Loesch et al, 2003;Ennis et al, 2006;Allen et al, 2007;Hunter et al, 2008a,b;Rodriguez-Revenga et al, 2008;Roberts et al, 2009bRoberts et al, , 2016Seltzer et al, 2012;Yang et al, 2013;Kraan et al, 2014;Mailick et al, 2014;Wheeler et al, 2014;Shelton et al, 2016;Klusek et al, 2018b;Nayar et al, 2019;Winston et al, 2020). Severity of executive dysfunction (Hunter et al, 2008b;Goodrich-Hunsaker et al, 2011a,b;Klusek et al, 2020), psychiatric symptoms (Allen et al, 2007;Roberts et al, 2009a;Seltzer et al, 2012), and social-communication differences (Schneider et al, 2016;Klusek et al, 2018a;Maltman et al, 2021) have linear and curvilinear associations with increased CGG repeat count in female PMCs. Although these findings may help account for variability in neuropsychiatric features, few studies have explored whether heterogeneous presentation among female PMCs may reflect differential presentation of these features in unique subgroups.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Together with certain personality styles (e.g., social reticence, rigid personality), pragmatic differences comprise a constellation of traits that mirror the defining characteristics of ASD and are referred to collectively as the Broad Autism Phenotype (BAP) (20,53). Features of the BAP (and pragmatic differences in particular) have also been observed among mothers of individuals with FXS, who are carriers of the FMR1 gene in its premutation state (20,54). Some evidence suggests that parent pragmatic language differences are associated with pragmatic language development in children with ASD and FXS (45,55,56).…”
Section: Introductionmentioning
confidence: 99%